2016
DOI: 10.2147/ijwh.s110202
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of social support among women presenting for obstetric fistula repair surgery in Tanzania

Abstract: ObjectiveAn obstetric fistula is a childbirth injury resulting in uncontrollable leakage of urine and/or feces and can lead to physical and psychological challenges, including social isolation. Prior to and after fistula repair surgery, social support can help a woman to reintegrate into her community. The aim of this study was to preliminarily examine the experiences of social support among Tanzanian women presenting with obstetric fistula in the periods immediately preceding obstetric fistula repair surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Notably, some of the more recent papers respond to the historically dominant narrative describing the heavy stigma women with obstetric fistula face by depicting contrasting experiences [47,88,89]. For example, in their study in Tanzania, Dennis et al [47] emphasize the helpful roles that the wider family plays for many women, even when husbands are not supportive. They also found that problems with husbands frequently predated the fistula, and were not the result of the morbidity alone.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, some of the more recent papers respond to the historically dominant narrative describing the heavy stigma women with obstetric fistula face by depicting contrasting experiences [47,88,89]. For example, in their study in Tanzania, Dennis et al [47] emphasize the helpful roles that the wider family plays for many women, even when husbands are not supportive. They also found that problems with husbands frequently predated the fistula, and were not the result of the morbidity alone.…”
Section: Resultsmentioning
confidence: 99%
“…Female genital fistula is often a direct result of inadequate obstetric health services for women with obstructed labor; congenital, iatrogenic, and genital trauma represent other less frequent causes . Women with fistula suffer physical, socioeconomic, and psychological consequences and experience a high level of disability, which further limits their access to adequate health services and skilled surgical care . The Democratic Republic of Congo (DRC) is a country characterized by weak maternal health indicators; the World Bank reports a fertility rate of 6 births per woman and a maternal mortality ratio of 550 per 100 000 live births .…”
Section: Introductionmentioning
confidence: 99%
“…The Tanzanian government has attempted to identify all girls and women with untreated fistula and refer them to healthcare facilities for free surgical repair [11]. Repair of fistula is recommended within 3 months of woman first experiencing fistula symptoms; if women delay seeking treatment for more than 3 months, the condition tends to be difficult to repair and results in more delay in healing and possible reoccurrence of fistula [12, 13]. Surgical fistula repair has a success rate of up to 90% and has been shown to have a positive impact on women’s lives by improving their economic status, physical condition and interpersonal relationships [12].…”
Section: Introductionmentioning
confidence: 99%